2017
DOI: 10.1099/jmm.0.000462
|View full text |Cite
|
Sign up to set email alerts
|

Effects of olanexidine gluconate on preoperative skin preparation: an experimental study in cynomolgus monkeys

Abstract: PurposeTo determine the bactericidal efficacy of a new topical antiseptic for preoperative skin preparation, olanexidine gluconate (development code: OPB-2045G), against transient or resident bacterial flora on the skin of cynomolgus monkeys.MethodologyAfter measuring baseline bacterial counts on test sites marked on the abdomens, we applied olanexidine, chlorhexidine or povidone–iodine. After 10 min (fast-acting effect) and 6 h (long-lasting effect), bacterial counts were measured again and log10 reductions w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 27 publications
(15 reference statements)
0
24
0
Order By: Relevance
“…These data were consistent with previous reports on the activity of chlorhexidine gluconate. 17,18) Our data showed that olanexidine gluconate has strong bactericidal activity and broad antibacterial and antifungal spectra. Hagi et al reported that bactericidal activity of olanexidine gluconate against various bacterial species was compared to CHG and PI by determination of minimum bactericidal concentration.…”
Section: Resultsmentioning
confidence: 83%
“…These data were consistent with previous reports on the activity of chlorhexidine gluconate. 17,18) Our data showed that olanexidine gluconate has strong bactericidal activity and broad antibacterial and antifungal spectra. Hagi et al reported that bactericidal activity of olanexidine gluconate against various bacterial species was compared to CHG and PI by determination of minimum bactericidal concentration.…”
Section: Resultsmentioning
confidence: 83%
“…8,32,33 Studies comparing different presurgical skin asepsis protocols in veterinary medicine are scarce. 9,10,12,29,30,[34][35][36][37][38] Commonly used methods involve a 5-minute preparation with mechanical scrubbing of the skin, during which the scrubbing procedure is repeated at least 3 times. [9][10][11][12] For our study design, CHX scrubbing was repeated 5 times because, in our hospital, we scrub twice in the preparation room and then 3 times in the operating room.…”
Section: Discussionmentioning
confidence: 99%
“…Olanexidine gluconate is a novel antimicrobial compound developed by Otsuka Pharmaceutical Factory, Inc. and has been used in Japan clinically for preoperative skin preparation [Product name: Olanedine Antiseptic Solution 1.5% (OLG)] (Hagi et al 2015;Inoue et al 2015;Nakata et al 2017). The virucidal efficacy of OLG against feline calicivirus at 60-s and 10 min were 0.60, and 2.85, respectively (unpublished data).…”
Section: Introductionmentioning
confidence: 99%